2021
DOI: 10.1021/acsami.1c11249
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of Interfaces and Defects: Cu/Oxygen Vacancy-Rich Cu-Mn3O4 Heterostructured Ultrathin Nanosheet Arrays for Selective Nitrate Electroreduction to Ammonia

Abstract: Achieving high efficiency in nitrate (NO 3 − ) to ammonia (NH 3 ) electrocatalysis requires the exploration of advanced electrocatalysts with a welldesigned composition and architecture. In this work, a facile one-step hydrothermal approach was developed for the construction of novel Cu/oxygen vacancy-rich Cu-Mn 3 O 4 heterostructured ultrathin nanosheet arrays on Cu foam (Cu/Cu-Mn 3 O 4 NSAs/CF). Two-dimensional ultrathin nanosheet arrays could increase the exposure of catalytically active centers, and the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 66 publications
1
70
0
Order By: Relevance
“…− -RR at PA-RhCu cNCs at 0.05 V applied potential are much higher than most reported values at various electrocatalysts (Table S1, Supporting Information), [29,[44][45][46][47][48][49][50][51][52] proving the high NO 3 − -RR activity of PA-RhCu cNCs. Obviously, the high apparent NO 3 − -RR activity of PA-RhCu cNCs directly benefits from the high ECASA derived from the unusual frame-like concave nanocube structure with hollow, pore-like and dendritic features.…”
Section: − -Rr Activity Of Pa-rhcu Cncs In Three Electrode Systemmentioning
confidence: 71%
See 3 more Smart Citations
“…− -RR at PA-RhCu cNCs at 0.05 V applied potential are much higher than most reported values at various electrocatalysts (Table S1, Supporting Information), [29,[44][45][46][47][48][49][50][51][52] proving the high NO 3 − -RR activity of PA-RhCu cNCs. Obviously, the high apparent NO 3 − -RR activity of PA-RhCu cNCs directly benefits from the high ECASA derived from the unusual frame-like concave nanocube structure with hollow, pore-like and dendritic features.…”
Section: − -Rr Activity Of Pa-rhcu Cncs In Three Electrode Systemmentioning
confidence: 71%
“…The fact indicates high NH 3 yield of NO 3 − ‐RR at PA‐RhCu cNCs originates from the KNO 3 electroreduction rather than N‐containing pollution species in the experimental environment. [ 55,56 ] Furthermore, it is observed that the NH 3 yield and faradaic efficiency of NH 3 for NO 3 − ‐RR at PA‐RhCu cNCs at 0.05 V applied potential are much higher than most reported values at various electrocatalysts (Table S1, Supporting Information), [ 29,44–52 ] proving the high NO 3 − ‐RR activity of PA‐RhCu cNCs. Obviously, the high apparent NO 3 − ‐RR activity of PA‐RhCu cNCs directly benefits from the high ECASA derived from the unusual frame‐like concave nanocube structure with hollow, pore‐like and dendritic features.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Moreover, Cu-based materials have attracted increasing attention for reduction of nitrate due to additional advantages, for instance, low cost compared with other noble metals. For example, Cu/Cu-Mn 3 O 4 /Cu foam, 20 defective CuO, 21 CuO nanowire arrays, 22 Cu nanosheets, 23 and three-dimensional Cu nanobelts were applied as the cathodes for nitrate reduction. 13 However, high selectivity and faradaic efficiency for ammonia were generally achieved on the above materials, as well as extra addition of Cl − usually being required to obtain high selectivity towards N 2 .…”
mentioning
confidence: 99%